OPTIC NEURITIS AND SEIZURES IN A PEDIATRIC PATIENT: IS IT RELATED TO NEUROMYELITIS OPTICA SPECTRUM DISORDER? - Wulandari, Lely Retno; Vierlia, Wino Vrieda (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Optic neuritis is a significant manifestation of central nervous system (CNS) demyelinating disorders, including Neuromyelitis Optica Spectrum Disorder (NMOSD). Pediatric cases are particularly challenging due to overlapping symptoms with other neurological conditions. Objective: This case report discusses a pediatric patient presenting with bilateral optic neuritis and seizures, raising suspicion of NMOSD. Methods: A 12-year-old male presented with acute bilateral vision loss and seizures. Comprehensive ophthalmological examinations, laboratory tests, and neuroimaging such as magnetic resonance imaging (MRI) and optical coherence tomography (OCT ) were performed. Due to financial constraints, specific NMOSD diagnostics, such as AQP4-IgG antibody testing, were not conducted. The patient was treated with high-dose intravenous methylprednisolone (IVMP) following the Optic Neuritis Treatment Trial (ONTT) protocol and valproic acid for seizure control. Results: Significant improvement in visual acuity was observed within five days of IVMP treatment. The right eye (RE) improved from hand motions to 6/48, and the left eye (LE) from hand motions to 6/144. By day eight, further improvement in visual acuity was noted. Seizures were effectively controlled with valproic acid, and no additional neurological symptoms were reported during follow-up. MRI showed no characteristic lesions, and laboratory results were within normal limits. Conclusion: The success of treatment despite diagnostic limitations suggests that with timely intervention, favorable outcomes are possible even in challenging settings. Future research should focus on developing accessible diagnostic tools and protocols that can be implemented in resource-limited environments. Additionally, awareness and training for healthcare providers in such settings are essential to improve early recognition and treatment of NMOSD.